Exploring child protection social workers' perceptions of how their experience of work and wellbeing influence each other - Stander, Janita (Department of Social Development, 2023)
This qualitative study explored child protection social workers' perceptions of how their working experience and wellbeing positively and negatively influence each other. It also further considered child protection social workers' perceptions of the support currently available to them as well as any other supportive measures they require in order to cope effectively with their work demands while maintaining a good sense of well-being. The research was conducted in a Non-Governmental Organisation and permission was granted by the research site to conduct the qualitative study with child protection social workers employed by them. Purposive sampling was used to select the 20 participants and semi-structured online interviews were conducted with these participants. The interviews were recorded, transcribed and then translated from Afrikaans to English. Tesch's (1990) data analysis model was utilised in order to analyse data obtained from the interviews. The findings of this study illustrated the mutual influence that participants' work experience and wellbeing have on each other. Positive relationships with colleagues, supervision, training, time off, experience, protection of children and the unpredictability of the job were highlighted as factors positively influencing participants' wellbeing. Conversely, participants' wellbeing was also negatively influenced by certain challenges encountered at work such as changes due to Covid 19, unpredictability of the job, high caseloads, lack of resources, high level of responsibility, threats to personal safety, repeated exposure to trauma, supervision and the expectations of communities and other stakeholders. Supportive personal relationships, selfcare, spirituality, a positive attitude, boundaries and self-assertiveness enabled participants to cope with work stressors. Certain emotional health factors such as stress and low mood levels negatively influenced participants' work experience. Participants highlighted the need for certain supportive practices such as teambuilding activities, access to debriefing services and a space for reflection. Recommendations were made around the implementation of regular teambuilding activities, provision of debriefing services, continuation of time off policies as well as training opportunities. Recommendations were also made for future research.